Response to Lynn Cavanagh - Krebs, Harald (Canadian University Music Review / Revue de musique des universités canadiennes, 2002)
Krebs's unusual monograph demonstrates that the writing of pure music theory remains an essential enterprise—particularly in the relatively neglected rhythmic domain—but only if the reader undertakes active reading and has prior knowledge of how the music goes. Within the monograph, perpetuation of the image of the misunderstood and suffering artist as a clue to the extramusical meaning Schumann associated with metrical dissonance leads to biased results. This essay's supplementary analysis of the first movement of Schumann's Symphony No. 3, informed by the history of ideas, proposes that in this movement metrical dissonance is used to reinterpret an emblem of the past so as to convey a vision of the future.